2009
DOI: 10.1007/s12098-009-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adolescent girls from an urban slum area in South India

Abstract: It is concluded that there is a high prevalence of under nutrition among adolescent girls in this slum community. Health education and nutrition interventions are needed on priority basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 6 publications
4
40
2
Order By: Relevance
“…The present results confirm the difference of the social class on the nutritional and health status of young adult females as shown by Gupta et al 200910.The significantly lower weight and BMI of these girls belonging to the lower SES is attributed to the poverty and the social class of the subjects, also supported by K. Prashant et al 2009 [11] , Sanjeev M C et al 2008 [12] and ME Bentley et al 2003 [13] . …”
Section: Resultssupporting
confidence: 88%
“…The present results confirm the difference of the social class on the nutritional and health status of young adult females as shown by Gupta et al 200910.The significantly lower weight and BMI of these girls belonging to the lower SES is attributed to the poverty and the social class of the subjects, also supported by K. Prashant et al 2009 [11] , Sanjeev M C et al 2008 [12] and ME Bentley et al 2003 [13] . …”
Section: Resultssupporting
confidence: 88%
“…Energy deficient refers to the BMI for-age Z-score below -2SD i.e., the energy requirement is not sufficient A study on . Nutri onal Status of Adolescent Girls from an Urban Slum Area in South India concluded that there is a high prevalence of stun ng (47%), of underweight (42.6%) and of thinness 4 (20.6%) among adolescent girls in this slum community.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence stunting is also recognized to be manifested due to prolonged food deprivation or illness 4 . A number of studies from India have reported that the prevalence of undernutrition poses a major nutritional threat to adolescents 5,8,10,[17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%